Sum of a number of terms in a.p., Mathematics

We know that the terms in an A.P. are given by

a, a + d, a + 2d, a + 3d, ........ a + (n - 2)d, a + (n -  1)d

The sum of all these terms which is denoted by "S" is given by

  S = n/2 {2a + (n - 1)d}

This is obtained as follows. We know that

S       =       (a) + (a + d) + (a + 2d) + (a + 3d) + ..... +

                   {(a + (n - 2)d)} + {(a + (n - 1)d)}

Now we reverse the order and write it as shown below.

S       =       (a + (n -1) d) + (a + (n - 2) d) + ......... +

                   (3d + a) +  (2d + a) + (d + a) + a

On adding the respective terms we get

2S     =       {a + a + (n - 1)d} + {a + d + a + (n - 2)d}

                   + ......... + {a + (n - 2)d  + a + d} +

                   {a + (n - 1)d + a} 

That is, we have:

2S     =       {2a + (n - 1)d} + {2a + d + (n - 2)d} +

                    ............... + {2a + d + (n - 2)d} +

                   {2a + (n - 1)d}

Further simplifying we obtain

2s     =       {2a + (n - 1)d} + {2a + d + nd - 2d} +.............. +

                   {2a + d + nd - 2d} + {2a + (n - 1)d}

On simplification we obtain

2s     =       {2a + (n - 1)d} + {2a + nd - d} + ......... +

                   {2a + nd - d} + {2a + (n - 1)d}

2s     =       {2a + (n - 1)d} + {2a + (n - 1)d} + ....... +

                   {2a + (n - 1)d} + {2a + (n - 1)d}

Since 2 + 2 + 2 + 2 = 2(1 + 1 + 1 + 1) = 2 x 4,

2a + (n - 1)d  multiplied n times will be  n.{2a + (n - 1)d}. Therefore,

         2s      =       n.{2a + (n - 1)d}

                            or

s

= n/2 {2a + (n - 1)d}       ............. (a)

Since l = a + (n - 1)d,  equation (a) is also written as

s

= n/2   {a + a + (n - 1)d}  or       

= n/2 {a + l}

Now we will find the sum of 20 terms when a = 5 and d = 2. Substituting these values in the formula, we obtain

s

= 20 /2 {2(5) + (20 - 1)2}
  = 480  

This problem can also be solved by finding the last term which in this case happens to be T20 and it is given by T20 = 5 + (20 - 1)2 = 43. Therefore,

s = n /2 {a + l}
  = 20 /2 {5 + 43} = 480.

We observe that both these methods are essentially the same. With this background let us look at few more examples.

Example 

For the series given below, find the 23rd and the 27th terms.

                   38, 36, 34, .............

We are given the first term that is a = 38. The common difference d is given by 36 - 38 = -2.  The 23rd term is given by

         T23    =       a + 22d

                   =       38 + 22(-2)  

                   =       38 - 44  = - 6  

Similarly the 27th term is given by

         T27    =       a + 26d

                   =       38 + 26(-2)

                   =       38 - 52

Posted Date: 9/13/2012 4:20:58 AM | Location : United States







Related Discussions:- Sum of a number of terms in a.p., Assignment Help, Ask Question on Sum of a number of terms in a.p., Get Answer, Expert's Help, Sum of a number of terms in a.p. Discussions

Write discussion on Sum of a number of terms in a.p.
Your posts are moderated
Related Questions
Vector Functions We very firstly saw vector functions back while we were looking at the Equation of Lines. In that section we talked about them as we wrote down the equation o

PROOF OF VARIOUS INTEGRAL FACTS/FORMULAS/PROPERTIES In this section we've found the proof of several of the properties we saw in the Integrals section and also a couple from t

Describe the Properties of Inequalities ? Postulate In comparing two quantities, say a and b, there are exactly three possibilities. (1) a is less than b. (a b)

how many times can u put 10000 into 999999

performs the mentioned operation and write the answers in standard form. ( -4 + 7 i ) + (5 -10 i ) Solution Actually there isn't much to do here other than add or subt

Inverse Cosine : Now see at inverse cosine.  Following is the definition for the inverse cosine.                         y = cos -1 x       ⇔ cos y = x                   for

Which expression has an answer of 18? Use the order of operations and try every option. The first option results in 14 since 2 . 5 = 10, then 10 + 4 = 14. This does not work. T

#question when equation of tangent T=0 and why